Typical Coal Mines in Hancheng Mining Area of China and its Management Reseach. Issue 1 (February 2021) - Zhang, Yao; Fu, Shaojun; Li, Ning; Hu, Zaiqiang
Abstract: In order to promote the work of prevention and management of coal mine water disaster in China, it took Panlong coal mine, Xiayukou coal mine and Xiangshan coal mine in Hancheng mining area as object of study. Methods of prevention and management of Ordovician limestone water inrush and water inrush from old and empty areas were put forward. Some examples were chosen to approve these methods' practicability. At last, enhancing management of coal mine and improving stuffs' comprehensive quality were proposed.